2011
DOI: 10.7238/rusc.v8i2.1069
|View full text |Cite
|
Sign up to set email alerts
|

Internationalization of Higher Education: Theoretical and Empirical Investigation of Its Influence on University Institution Rankings

Abstract: La internacionalización en la enseñanza superior: investigación teórica y empírica sobre su influencia en las clasificaciones de las instituciones universitarias ARTÍCULO

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 21 publications
0
29
0
3
Order By: Relevance
“…In fact, factors such as the number of students and faculty members play a particular role in globalization. The number of PhD students is important for further research and recruitment of faculty to study and teach at the Master's degree level; hence, for countries that intend to increase the number of nationally and globally reputable universities, we recommend that they expand research capacity and promote educational and research quality in their universities, especially as compared with other reputable universities (29,30). It can be concluded that getting a desired position based on the criteria and indices of global ranking system plays a significant role in quality promotion and globalization.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, factors such as the number of students and faculty members play a particular role in globalization. The number of PhD students is important for further research and recruitment of faculty to study and teach at the Master's degree level; hence, for countries that intend to increase the number of nationally and globally reputable universities, we recommend that they expand research capacity and promote educational and research quality in their universities, especially as compared with other reputable universities (29,30). It can be concluded that getting a desired position based on the criteria and indices of global ranking system plays a significant role in quality promotion and globalization.…”
Section: Discussionmentioning
confidence: 99%
“…Ranking has become increasingly important for universities because of external pressures, not least because overseas students use it to aid selection (Clarke, 2007;Barber et al, 2013). Internationally, international recruitment is seen as a measure of the competitive prowess and reputational strength of a university (Delgado-Márquez et al, 2011;Rauhvargers, 2013).…”
Section: Layer 3 Growing the International Enterprise Universitymentioning
confidence: 99%
“…The rapid changes made possible by globalization including increasing innovations and global interconnectedness have had a major impact on HE (Altbach et al, 2009;Delgado-Marquez et al, 2011). For some time now, the pressures and possibilities of an increasingly globalized world and an internationalized HE sector have led to a large number of changes.…”
Section: Introductionmentioning
confidence: 98%
“…The numbers of international students being admitted to universities has increased as more and more students are choosing 'to study abroad, enrol in foreign educational programmes and institutions in their home country, or simply use the internet to take courses at colleges and universities in other countries' (Delgado-Marquez et al, 2011, 268). International networking has become the norm and universities are signing more and more partnership agreements with institutions in other countries for joint research, teaching and student exchange, for example, and 'new values and perspectives' have entered 'academic endeavours in education and research' (Paulsdottir and van Liempd, 2012, 25; see also Delgado-Marquez et al, 2011). Other changes have included English becoming the 'lingua franca' of international HE, as it is in the sectors of finance, aviation and 'scientific communication' (Altbach and Knight, 2007, 291), with universities in non-English speaking countries now offering whole degree programmes taught in English.…”
Section: Introductionmentioning
confidence: 98%